Technological innovation and eco-efficiency in manufacturing companies: Does Co-innovation orientation matter? - (:unkn) unknown (Elsevier BV, 2024)
The rising need for sustainable development poses a critical challenge for manufacturing companies, requiring a fresh perspective on adopting greener practices. One recent approach to enhancing sustainability in manufacturing is the development of innova...
Keywords: Innovación tecnológica; Ecoeficiencia